Finite Element Analysis of Tribological Properties of Worm Gear Under Wet Condition - J. S. Bhat, B.U.Sonawane, M. R. Desai (International Journal of Advanced Science and Technology, 2020)
This research paper deals with FEA results related to tribological properties such as friction, wear, and lubrication of worm gear pair. A worm gear is having a very high reduction ratio in a single stage up to a 200:1 ratio. Due to sliding action between gear pair tribological properties mostly friction, wear, lubrication plays an important role in the performance of the worm gear. Energy wastage results in direct and indirect losses. Experimentation was carried out with Pin on Disc Tribometer to analyzed tribological properties of worm gear pair under wet condition. Ansys Workbench 19 was used to check the effect of tribological properties of worm gear pair under the same condition. In this research load, speed and time are considered as an input parameter and frictional force and wear are the output parameter. 16 to 22% of deviation between experimental result and simulation result.FEA method is an approximation method, so due to assumed data or inputs results are varying.